Pengaruh Model Pembelajaran PBL terhadap Kemampuan Berpikir Tingkat Tinggi Siswa pada Materi Pembelajaran Biologi di SMA Negeri 1 Tondano - Gabriel Stevan Legi; Mariana Rengkuan; Zusye Warouw (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study examines the effect of applying the Problem-Based Learning (PBL) learning model on students' high-level thinking skills on ecosystem materials at SMA Negeri 1 Tondano. This study uses an experimental method with a quasi-experimental design involving two groups of students: the experimental class (X.2) taught using the PBL model, and the control class (X.4) taught using conventional learning methods. The number of students in each class is 30 people. Data is collected through pretest and posttest to measure students' high-level thinking abilities. The analysis showed that the experimental class's average posttest score was 83.67, while the control class was 79.50. The independent t-test showed that the t-count value (2.073) was greater than the t-table (1.671) with a significance value of 0.043, which was smaller than 0.05, indicating a significant difference between the two groups. Based on these results, it can be concluded that applying the PBL model has a positive and significant effect on improving students' high-level thinking skills. These findings are consistent with previous research showing that the PBL model effectively improves students' critical and analytical thinking skills. Therefore, applying PBL can be an effective alternative to improve the quality of learning, especially in developing students' high-level thinking skills.